Conservative therapy in chronic renal failure - I Gde Raka Widiana I Gde Raka Widiana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1995)
Chronic renal failure is still a major health problem in medicine world. An adequate treatment could only retard the progress of renal failure and delay the course toward end-stage renal disease, a condition that requires maintenance dialysis or kidney transplantation.Managable factors should always be identified and promptly treated. Dietary therapy may be able to cope with uremic symptoms, perhaps retards the progress of renal failure and improves nutritional status. All above mentioned will improve morbidity and mortality of the patients. A proper antihypertensive regiment not only protect the kidneys through blood pressure reduction but also gives independent renoprotective effects by improvement of renal hffect and electrolyte balance.emodynamics without negative metabolic effect and electrolyte balance.Key Words: end-stage renal disease -- predialytic phase -- conservative treatment -- dietary management -- hypertension